The effect of additional resistance of air flow on the functioning parameters of the highly qualified rowers' outer respiration - Grechuha S.V; Bezkopylny O.O; Kovalenko S.O (Kharkov National Pedagogical University, 2010)
Influence of additional resistance the current of air is rotined on the feature of functioning of the system of the external breathing of sportsmen. In experiment 12 sportsmen took part 17-25 years. All sportsmen are candidates or sport masters. Experience of employments of sportsmen made 4-12 years. Tests were conducted in a preparatory period of annual cycle of training. The dynamics of changes speed of current of air is presented, ventilations of lights at peace and at the dosed physical loading. More effective for development of functional possibilities of respiratory muscles for sportsmen it is possible to count application of additional resistance on exhalation.